Non-invasive prenatal testing (NIPT): Combination of copy number variant and gene analyses using an "in-house" target enrichment next generation sequencing-Solution for non-centralized NIPT laboratory - Faldynová, Lucie; Walczysková, Sylwia; Černá, Dita; Kudrejová, Monika; Hilscherová, Šárka; Kaniová, Romana; Širůčková, Simona (Prenatal diagnosis, 2023)
OBJECTIVE: Recent studies have integrated copy number variant (CNV) and gene analysis using target enrichment. Here, we transferred this concept to our routine genetics laboratory, which is not linked to centralized non-invasive prenatal testing (NIPT) facilities. METHOD: From a cohort of 100 pregnant women, 22 were selected for the analysis of maternal genomic DNA (gDNA) along with fetal cell-free DNA. Using targeted enrichment, 135 genes were analyzed, combined with aberrations of chromosomes 21, 18, 13, X, and Y. The data were subjected to specificity and sensitivity analyses, and correlated with the results from invasive testing methods. RESULTS: The sensitivity/specificity was determined for the CNV analysis of chromosomes: 21 (80%/75%), 18 (-/82%), 13 (100%/67%), and Y (100%/100%). The gene detection was valid for maternal gDNA. However, for cell-free fetal DNA, it was not possible to determine the boundary between an artifact and a real sequence variant. CONCLUSION: The target enrichment method combining CNV and gene detection seems feasible in a regular laboratory. However, this method can only be responsibly optimized with a sufficient number of controls and further validation on a strong bioinformatic background. The present results showed that NIPT should be performed in specialized centers, and that its introduction to isolated laboratories may not provide valid data.
Keywords: volné cirkulující nukleové kyseliny; lidské chromozomy, pár 21; Pregnancy; Cell-Free Nucleic Acids; těhotenství; laboratoře; Laboratories; Chromosomes, Human, Pair 21; lidé; Female; DNA Copy Number Variations; ženské pohlaví; variabilita počtu kopií segmentů DNA; Humans; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing